Uncovering the Students’ Mathematical Concept Understanding Ability: a Based Study of Both Students’ Cognitive Styles Dependent and Independent Field in Overcoming the Problem of 3D Geometry - Sudirman Sudirman; Aloisius Loka Son; Rosyadi Rosyadi; Rizkiah Nurul Fitriani (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2020)
The present study aims at uncovering Mathematical Concept Understanding Ability in solving the problem of 3D Geometry from the perspective of both cognitive styles dependent and independent field. As the instrument, this study adopts Group Embedded Figure Test, Observation worksheet, test, interview, and documentation. In dealing with data analysis, it relies on qualitative analysis consisting data reduction, data display, and conclusion drawing. Based on the investigation, it could be inferred that the students with cognitive dependent field could solve the problem with 3D Geometry; however, they still need some improvements to realize a proper way in using such method. On the other hand, the students with cognitive independent field, they could correctly operationalize the 3D Geometry concept to solve the same problem. In addition, this study also recommends that to minimize the problem above, the teacher is supposed to give proportional distribution in implementing either individual or group task.